PEMETAAN KOMPETENSI DAN PENINGKATAN MUTU PEMBELAJARAN FISIKA SISWA SMA/MA DI KABUPATEN KUTAI BARAT PROVINSI KALIMANTAN TIMUR - Zeni Haryanto (Media Komunikasi Geografi, 2013)
Graduation rates of the National Examination SMA/MA in West Kutai district in 2011 were ranked the lowest in the province of East Kalimantan. This condition is quite alarming and illustrates the uneven quality of education in East Kalimantan. Therefore be made to improve and enhance the quality of education, especially in West Kutai district.The purpose of this study is to identify the factors that cause low student achievement of competencies SMA/MA in subjects who entered the National Exam and find a suitable alternative model to address the causes of low student achievement of competencies SMA/MA in these subjects.The method used in this study is the method of research and development (Research and Development) held a 2 year period. The data in this study were obtained from interviews, observation and documentation study on the implementation of eight components of national education standards in SMAN 1 Sendawar, SMAN 2 Sendawar, and SMA Surya Mandala, which is being sampled in this study. Data collection techniques used is triangulation. Data analysis was conducted qualitatively using USG(Urgent, Seriousness and Growth)analysis and fishbone analysis.The results showed that the main causes of low student competence in the SMA / MA in West Kutai District is a standard implementation of the learning process of nonconforming Permendiknas. To overcome this problem, the problem-solving model recommended as alternative form of the application of constructivism learning model and lesson study in SMA/MA in West Kutai. Key words: competencies mapping, the results of National Examination, the development of quality learning, Kutai Barat